Mind the Gap: Translation Automation and the Lure of the Universal - Cronin, Michael (TTR)

(untitled) (Association canadienne de traductologie, 2013)
A recurrent concern of Daniel Simeoni’s writings is the concealed or disguised cultural origins of theoretical reflection or absence of reflection on translation. Allying this concern to a discomfort around particular kinds of universalist claims, this article examines forms of translation thought and practice that have emerged in the digital age. Two approaches to thinking about translation, “massive” thinking, and “detailed” thinking are used to situate particular kinds of translation practice in the era of automation and semi-automation. The strategic importance of detail in translation practice is located within the rising popularity of gist or indicative translation. Underlying both the “massive” and “detailed” approaches to translation, it is argued, are two different approaches to the question of the universal. The tension between easy universalism and difficult universalism is seen as bound up with projections of power and influence from which, as Simeoni repeatedly argued, translation and thinking about translation are not immune. In order to further develop the implications of difficult universalism for translation thinking and practice, the notion of “gap” is opposed to that of difference. The idea of “gap” avoids the reifying thrust of typicality that often underlies the invocation of difference and favours not so much the celebration of identity as the cultivation of fecundity. In this view, translators look to languages and cultures not so much for values as for resources. Where these “gaps” might be located is, of course, a source of endless conjecture but it is argued that in translation practices in the digital age, one place to look is in the debates around quality and what quality might mean in a digital age. The challenge quality poses for extensive universality is framed within Simeoni’s notion of the translator as borderline agent.